Implementasi Kuliah Pengabdian Masyarakat (KPM) Internasional Mahasiswa FEBI UIN Ar-Raniry sebagai Media Diplomasi Ekonomi dan Pendidikan: Studi Kasus di Hatyai, Thailand - Jauza Nuha; Zulvia Maika Letis; Muhammad Arifin; Fitria Rizkia Amanda; Kevin Fathuriansyah; Miftahul Jannah; Mutiara Nabila; Rahma Sarita Maulida; Rifqi Aldian; Siti Humairah (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
KPM Internasional is a form of student engagement that integrates academic, social, and cultural dimensions across national boundaries. This study aims to analyze the implementation of the International KPM as a medium for economic and educational diplomacy, using a case study in Hatyai, Thailand. The research employed a qualitative descriptive approach through participatory observation, in-depth interviews, and document analysis. The findings reveal that the KPM program in Hatyai not only strengthens academic collaboration between Indonesian and Thai universities but also creates opportunities for cooperation in the fields of creative economy, local trade, and halal product promotion. Moreover, the program plays a significant role in fostering soft diplomacy through cultural exchange, language interaction, and the dissemination of moderate Islamic values relevant to the Southern Thai context. Therefore, the International KPM serves as an effective instrument for expanding educational and economic networks while enhancing Indonesia’s positive image in the global arena.